Examining changes in occupational participation in forensic patients using the Model of Human Occupation Screening Tool. (December 2016) - Fan, Chia-Wei; Morley, Mary; Garnham, Mike; Heasman, David; Taylor, Renee
Introduction: In occupational therapy, there has been an increased interest in patients' occupational participation within forensic settings. This retrospective study involved a longitudinal analysis of occupational participation within six forensic hospitals in England. The aim was to contribute to the understanding of forensic patients' occupational participation over a two-year period. Methods: The Model of Human Occupation Screening Tool (MOHOST) was rated by 78 occupational therapists on 489 patients in low and medium secure units who were receiving occupational therapy over two years. The many-faceted Rasch Model was used to convert their MOHOST scores at each time point into interval scales. Regression analysis was used to examine changes in occupational participation over time. Results: Patients' overall occupational participation improved over time. Specifically, participation improved in five of the six MOHOST subdomains, which included their motivation for occupation, pattern of occupation, communication/interaction skills, process skills, and environment. Patients did not demonstrate significant change in their motor skills, which varied as expected. In addition, patients in low secure units had better occupational participation than those in medium secure settings. Conclusion: Our findings indicated improvements in the patients' occupational participation over the 2-year period. Further investigations are needed to understand factors contributing to change.